صفدر زیدی کے ناول "بھاگ بھری" کا مذہبی اور سیاسی بیانیوں کے تناظر میں تجزیاتی مطالعہ: A Critical Study of Safdar Zaidi's Novel 'Bhag Bhari' in the Context of Religious and Political Narratives (Research Journal Tahqeeqat, 2025)
Nuclearization and extremism are intricately linked to racial, linguistic, and religious sectarianism. In countries where clandestine forces exploit religious education to manipulate children's minds, stripping them of innocence and turning them into savages, sectarian and political biases become so entrenched that third-party interests can capitalize on them. Terrorism and suicide bombings are manifestations of a fanatical mindset, fueled by training that numbs young minds to guilt. The escalating tensions and extremism between Pakistan and India are also driven by these very sectarian, political and linguistic prejudices, further exacerbated by clerics and pundits. In this context, Safdar Zaidi's novel "Bhag Bhari" sheds light on the covert agencies that sow seeds of sectarianism and violent ideologies among the youth, serving specific agendas.Through its narrative, the novel exposes the dark reality of madrasses and extremist groups and their involvement in brainwashing young minds to perpetrate violence and terrorism.The article also discusses the novel’s futuristic and realistic aspects, which depict the devastating consequences of nuclear war and environmental pollution.Overall, the novel serves as a warning about the danger of extremism and the importance of promoting peace and understanding between nations.